2014
DOI: 10.1155/2014/659270
|View full text |Cite
|
Sign up to set email alerts
|

Massive Submandibular Sialolith: Complete Radiographic Registration and Biochemical Analysis through X-Ray Diffraction

Abstract: Sialolithiasis is a pathologic condition that affects 60 million people per year, which is caused by the presence of calcified structures, named sialoliths, inside the salivary glands and their salivary ducts. Despite the large incidence of sialolithiasis, its etiology is still unknown. In the present case report, a 47-year-old female patient, presenting with local pain and hampered mouth opening, underwent a surgical approach for the removal of a 20 mm sialolith, which was further analyzed through X-ray diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
0
11
0
5
Order By: Relevance
“…Some authors have reported that submandibular sialolithiasis causes a reduction of the salivary flow 15 , while others as Gaetti et al state that salivary flow is increased due to glandular enlargement 6,16 . In the present case, despite that a sialometry was not performed to check if there was a reduction of the salivary flow, no clinical or symptomatic evidence of changes or alterations occurred in the flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported that submandibular sialolithiasis causes a reduction of the salivary flow 15 , while others as Gaetti et al state that salivary flow is increased due to glandular enlargement 6,16 . In the present case, despite that a sialometry was not performed to check if there was a reduction of the salivary flow, no clinical or symptomatic evidence of changes or alterations occurred in the flow.…”
Section: Discussionmentioning
confidence: 99%
“…Calculi often cause obstruction of the salivary f low, causing pain, inf lammation and recurrent infections, a condition known as sialolithiasis 3 . Sialolithiasis affects 60 million people a year 4 , two men for every woman, and is most prevalent in adults 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Large salivary gland sialoliths, which are larger than 15 mm are considered rare. [5] Sialolithiasis usually presents with pain and infl ammation but in few cases infection of the main gland may present. The exact etiology and pathogenesis of salivary calculi is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Bu geçici ağrının sebebinin sialolitin, wharton kanalını tam olarak tıkamaması ve kanalın bir kısmından tükürük akışının sağlanması olduğu düşünülmektedir. Ağız kuruluğu (37), ağız tabanında farkedilebilir şişlik (32), submandibular bölgede şiddetli ağrı ve ağız açmada kısıtlılığa bağlı konuşmada güçlüğe sebep olan (38), olgular da bildirilmiştir.…”
Section: şEkilunclassified